Enlightening the coastal communities of Bengkalis Island on climate change policies - Zulkifli, Afni; Hakim, Triono Dul; Amelia, Vita (Community Empowerment, 2021)
Coastal communities are some of the most vulnerable groups to the effects of climate change. The Non-Governmental Organization of the Environmental Malay Youth Institute (LSM IPMPL), a partner of the three villages on Bengkalis Island, has traced the communities’ ignorance of climate change policies to the poor digital literacy of community members. This has had an impact on the involvement of community components and local village governments in climate change mitigation and adaptation efforts. This community service provides assistance, socialization, and training to improve the literacy of the coastal communities of Bengkalis Island, especially as it concerns their access to climate change policies. The results of this activity show an increase in the communities’ knowledge, abilities, skills, and digital awareness of the government's efforts towards forming a climate-resilient society. Furthermore, the activity produced social impact as it increased peace, improved the community's economy and improved the quality of the community's living environment.